Tertiary Institutions and Development in Rural Communities: Role of Federal University Oye-Ekiti, Ekiti State, Nigeria - Akindola, Rufus B; Ojo, Shina J (Asian Journal of Agriculture and Rural Development, 2020)
This paper examines the economic impact of Federal University Oye-Ekiti, Ekiti State, Nigeria on its host communities in Oye and Ikole towns since inception. The study sets out with a major objective of determining whether the establishment of the university would organically lead to the development of its host communities. Quantitative and qualitative techniques were adopted for research design while the stratified sampling technique was used in administering the questionnaire for the study. The results show that while the establishment of tertiary institutions has a potential to increase household income in rural communities where they are located, it does not necessarily lead to the development of these communities in terms of basic health care facilities, primary education centers, good road networks and improved standard of living.